Implementation of the Political Public Relations Approach of DPD PKS Bekasi Regency in Fostering and Maintaining Good Relations with the Public - Bambang Dwinanto; Harmonis (Institute of Computer Science (IOCS), 2022)
For political parties, the Public Relations (PR) approach has a very important and strategic role, especially in fostering and maintaining good relations with the community. to the public to be better known and trusted so that it has a positive image. Likewise with DPD PKS Bekasi Regency which uses a PR approach as one of its strategies. With a fairly loyal mass base, the development of a political community is the strategy chosen by the Bekasi Regency PKS DPD to foster and strengthen the PKS volunteer base in the Bekasi Regency area. This study aims to describe the implementation of the PR DPD PKS approach in Bekasi Regency in fostering good relations with the public. The method used in this research is descriptive qualitative. Data collection was obtained through interviews and documentation. From this research, it shows that the PR approach taken by DPD PKS Bekasi Regency in fostering good relations with the public is by building a political community.